SAT-554 Genetic Profile of Early-Onset Aldosterone-Producing Adenomas - Baker, Jessica E (J Endocr Soc, 2020)
Background: Aldosterone-producing adenoma (APA) is a major subtype of primary aldosteronism (PA) which is the most common cause of endocrine-related hypertension. The Endocrine Society clinical practice guideline suggests that young patients (< 35 years old) with a CT-detected adrenocortical adenoma and typical phenotype of PA may not need adrenal venous sampling prior to adrenalectomy. In recent years, aldosterone-driver somatic mutations have been identified in APA, and prevalence studies suggest potential effects of patient age and sex. However, the rare nature of early-onset PA has prevented a detailed study of the histologic characteristics and aldosterone-driver somatic mutations in adrenal tumors from these patients. Objective: To determine histologic and somatic mutation profile in early-onset APA. Methods: Fifty-five formalin-fixed paraffin-embedded (FFPE) adrenals from patients at the age of 35 years old or younger who underwent adrenalectomy at the participating centers were studied (45 women, 9 men, and 1 unknown sex). CYP11B2 immunohistochemistry (IHC)-guided tumor capturing was used to selectively obtain DNA from APA. Mutation status was determined either by Sanger sequencing or targeted next-generation sequencing. Results: CYP11B2 IHC identified APAs in all adrenal specimens. Solitary APAs were found in 53 adrenals. One adrenal had multiple APAs and one had a dominant CYP11B2-negative tumor and a smaller APA. In total, DNA from 57 APAs were sequenced. Two APAs were excluded from the analysis due to low sample quality. In 52 of the 55 APAs, somatic mutations were identified in one of the aldosterone-driver genes or CTNNB1 gene, encoding β-catenin. The most common genetic alteration was seen in KCNJ5 (37/55, 67%), followed by CACNA1D (7/55, 13%), ATP1A1 (3/55, 5%), CTNNB1 (3/55, 5%), and ATP2B3 (2/55, 4%). No sex difference in the prevalence of KCNJ5 mutation was observed in this age group. Conclusion: The majority of adrenals from early-onset PA patients had a solitary APA. Regardless of sex, the most common genetic cause of early-onset APA was somatic mutations in KCNJ5.